Social innovation in Africa a practical guide for scaling impact - Ndidi Okonkwo Nwuneli (London ; New York Routledge, Taylor & Francis Group, 2016)
Encouraged by the emergence and early impact of social innovators on the African Continent, but frustrated by the slow pace of large scale change, this book is focused on filling the knowledge gap for those tackling Africa?s serious social problems.
Includes bibliographical references (pages 164-167) and index.
Keywords: Social entrepreneurship--Africa.